KAJIAN PARTIAL BAKTERI PENAMBAT NITROGEN NON SIMBIOTIK ASAL RHIZOSFER TANAMAN GAMAL SEBAGAI PLANT GROWTH PROMOTING PADA LAHAN SISTEM TIGA STRATA PECATU - N.G.K. Roni; S.A. Lindawati (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
Gamal is one of the tropical forages that can still grow and produce f on dry land in the hot season, while other plants, especially the grass has dried so it needs to be examined soil conditions in the rhizosphere. A study aimed at studying soil conditions in rhizosphere of gamal plants and obtaining isolates of non symbiotic nitrogen-fixing bacteria from gamal rhizosphere that function as Plant Growth Promoting on three strata land (STS) Pecatu, Bukit jimbaran, Badung, Bali. The research begins with observation of soil texture and color, soil structure determination and water content, pH, and soil total plate count, followed by calculation of non-symbiotic N fixing bacteria,, isolation, gram staining test, fermnetatif test, and catalase test. The results showed that soil characteristics of STS Pecatu land include clay clay texture, compact structure, brownish color, pH 6.79-7.40, water content 14,19-18,12, STS Pecatu land including fertile land with total plate count 1.65x 107 cfu/g, and 6 non-symbiotic non-beneficial bacterial inhibitors were suspected from the genus Azotobacter sp, with colonies of 83 x 105 cfu/g. Based on the result of the research, it can be concluded that the soil of STS Pecatu land including fertile land with total plate count 16,5 x 106 cfu/g, and found 6 isolate of non-symbiotic N fixing bacteria from genus Azotobacter sp, with number of colony 83 x 105 cfu/g. Keywords: Non-symbiotic N-fixing bacteria, Three-Strata System, Pecatu